GAMBARAN PENGETAHUAN IBU TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA 9 BULAN DI RW 4, DESA JUNREJO, KOTA BATU - Kristanti, Eny; Maulidia, Rahmawati (Journal of Nursing Care and Biomoleculer, 2019)
Introduction: A mother is expected to know more and play a role in the process of growth and development of children and become one of the factors that influence the process of growth and development of 9-month-old children. Knowledge about 9-month-old children development is also very important because it can direct mothers to interact more with children so that they tend to create an environment that is suitable for the emergence of children's abilities. The purpose of this study was to determine the extent of the knowledge of parents in the gross motoric development of 9-month-old children. Method:This research method uses a qualitative case study with the technique of collecting data using a voice recorder for in-depth interviews with one participant. Result and analysis: The results of this study include: (1) Knowledge of children's gross motor development; (2) Knowledge of the risks of delays in gross motor development and their causes, as well as actions to be taken when knowing signs of delay in gross motor development in children; (3) Knowledge of prevention measures for gross motor development delay to optimize the gross motoric development of children. Discussion: Participants and the community are expected to be more active in looking for information about child development specifically for the gross motor development.